Pengujian Konstitusionalitas Hak atas Lingkungan Hidup yang Baik dalam Kasus Pencemaran Lintas Batas: Telaah terhadap Prinsip Kedaulatan Negara - Rena Zulfaidah; Utang Rosidin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the constitutional review of the right to a good and healthy environment as guaranteed under Article 28H paragraph (1) of the 1945 Constitution of Indonesia in the context of transboundary environmental pollution, with a focus on the interpretation of state sovereignty. Transboundary pollution raises serious legal challenges due to the limitations of national jurisdiction in protecting citizens’ constitutional rights from environmental harm originating outside state territory. This research employs a normative legal method using statutory, conceptual, and case approaches by analyzing the 1945 Constitution, environmental legislation, and relevant Constitutional Court decisions. The findings indicate that a narrow and territorial interpretation of state sovereignty may undermine the effective protection of environmental rights. Therefore, the Constitutional Court is encouraged to adopt a progressive constitutional interpretation that reconceptualizes sovereignty as a protective constitutional obligation (state obligation) encompassing transnational dimensions, in order to ensure the effective fulfillment of citizens’ environmental rights.